2016
DOI: 10.3389/fnhum.2016.00258
|View full text |Cite
|
Sign up to set email alerts
|

bihemispheric-tDCS and Upper Limb Rehabilitation Improves Retention of Motor Function in Chronic Stroke: A Pilot Study

Abstract: Background: Single sessions of bihemispheric transcranial direct-current stimulation (bihemispheric-tDCS) with concurrent rehabilitation improves motor function in stroke survivors, which outlasts the stimulation period. However few studies have investigated the behavioral and neurophysiological adaptations following a multi-session intervention of bihemispheric-tDCS concurrent with rehabilitation.Objective: This pilot study explored the immediate and lasting effects of 3-weeks of bihemispheric-tDCS and upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…Moreover, cerebral functional magnetic resonance imaging (fMRI) showed a stronger activation of the ipsilesional primary and premotor cortex during paced movements of the affected limb in the real stimulation group only. The same gain of function was obtained by others (Stagg et al, 2012 ; Goodwill et al, 2016 ), but in this last study, patients were separated into three groups evaluating separately the three conditions (cathodal vs. anodal vs. sham stimulation) although a lesser effect on hand motor deficit was observed (5–10%). In the same line, Rocha et al ( 2016 ) compared these three strategies to constraint induced movement therapy, in order to reinforce the “rebalancing” of cortical excitability between the two hemispheres.…”
Section: Non-invasive Brain Stimulation (Nibs) In Strokesupporting
confidence: 78%
“…Moreover, cerebral functional magnetic resonance imaging (fMRI) showed a stronger activation of the ipsilesional primary and premotor cortex during paced movements of the affected limb in the real stimulation group only. The same gain of function was obtained by others (Stagg et al, 2012 ; Goodwill et al, 2016 ), but in this last study, patients were separated into three groups evaluating separately the three conditions (cathodal vs. anodal vs. sham stimulation) although a lesser effect on hand motor deficit was observed (5–10%). In the same line, Rocha et al ( 2016 ) compared these three strategies to constraint induced movement therapy, in order to reinforce the “rebalancing” of cortical excitability between the two hemispheres.…”
Section: Non-invasive Brain Stimulation (Nibs) In Strokesupporting
confidence: 78%
“…Rabadi and Aston (2017) demonstrated large effect size improvements in motor function in eight participants with severe motor impairments after acute stroke after applying tDCS for 30 min with 3 h of inpatient rehabilitation therapy, compared to a control group who received sham tDCS and therapy [ 53 ]. Several studies have demonstrated retained improved motor abilities between 3 weeks and 3 months post-intervention in chronic stroke after a treatment that combined physical therapy with tDCS stimulation [ 12 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…39 The inter-hemispheric differences in gamma band absolute power after immobilization are justified by the ability of the hemispheres to mutually influence their functions through the corpus callosum. 4,40,41 These findings may have a bearing on the applicability of therapies such as transcranial magnetic stimulation, constraintinduced movement therapy, which are widely used in the rehabilitation of stroke [42][43][44] and cerebral palsy. [45][46][47] Some studies even indicate the possibility of using the EEG as a central nervous system dysfunctions marker.…”
Section: ■ Discussionmentioning
confidence: 99%